A study on the arrival time of ultrasonic waves in concrete material - Farah Aina, Mohamad Jamal; Ruzairi, Abdul Rahim; Nasarudin, Ahmad; Juliza, Jamaludin; Fazlul Rahman, Mohd Yunus; Yasmin, Abdul Wahab; Nur Arina Hazwani, Samsun Zaini; Rajan, Navintiran; Ahmad Ridhwan, Wahap (Springer Science and Business Media Deutschland GmbH, 2022)
Concrete is one of the most critical materials being used in construction project. Ultrasonic testing is a conventional non-destructive test method, that is adopted to evaluate the condition and quality of concrete structure. This is important to ensure the strength and resilience of built structures. This paper aims to assess the arrival time of the ultrasonic waves in concrete structure by employing ultrasonic through-transmission method. A simulation study was performed in COMSOL Multiphysics software. Data were collected and structured into three sections, including in homogenous concrete model, as well as concrete model with inclusion of air voids and cracks. This study investigates the influence of size of air voids and position of cracks on the arrival time of the received ultrasonic signal. The waves diffraction at the defects increase the arrival time of the received signal.